Use Of Music Pedagogy Experiences In Improving The Professional Skills Of Music Teachers Of General Secondary Schools - Ma’rufjon Ashurov Abdumutalibovich (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This scientific article was published on the basis of the principles of using music pedagogy experiences in improving the professional skills of music teachers of general secondary schools at the end of the dissertation work.